WEBVTT
00:00:00.501 --> 00:00:11.901
Find the length of the curve with parametric equations π₯ equals three cos π‘ minus cos three π‘ and π¦ equals three sin π‘ minus sin three π‘, where π‘ is greater than or equal to zero and less than or equal to π.
00:00:12.121 --> 00:00:26.111
We recall that the formula we used to find the arc length of a curve defined parametrically for values of π‘ from πΌ to π½ is the definite integral between πΌ and π½ of the square root of dπ₯ by dπ‘ squared plus dπ¦ by dπ‘ squared with respect to π‘.
00:00:26.291 --> 00:00:33.141
In this case, π₯ is equal to three cos π‘ minus cos three π‘ and π¦ is equal to three sin π‘ minus sin three π‘.
00:00:33.291 --> 00:00:38.431
And weβre interested in the length of the curve between π‘ is greater than or equal to zero and less than or equal to π.
00:00:38.711 --> 00:00:41.971
So weβll let πΌ be equal to zero and π½ be equal to π.
00:00:42.151 --> 00:00:45.661
Weβre also going to need to work out dπ₯ by dπ‘ and dπ¦ by dπ‘.
00:00:45.781 --> 00:00:51.511
And so, since weβre working with trigonometric expressions, we recall the derivative of cos of ππ‘ and sin of ππ‘.
00:00:51.651 --> 00:00:57.901
They are negative π sin of ππ‘ and π cos ππ‘, respectively, for real constant values of π.
00:00:58.211 --> 00:01:04.341
This means dπ₯ by dπ‘ is negative three sin π‘ minus negative three sin three π‘.
00:01:04.341 --> 00:01:07.011
And of course, that becomes plus three sin three π‘.
00:01:07.241 --> 00:01:11.361
Similarly, dπ¦ by dπ‘ is three cos π‘ minus three cos three π‘.
00:01:11.411 --> 00:01:15.691
Before we substitute into the formula, weβre actually going to square these and find their sum.
00:01:16.121 --> 00:01:25.431
Negative three sin π‘ plus three sin three π‘ all squared is nine sin squared π‘ minus 18 sin π‘ sin three π‘ plus nine sin square three π‘.
00:01:25.571 --> 00:01:35.401
Then, three cos π‘ minus three cos three π‘ all squared is nine cos squared π‘ minus 18 cos π‘ cos three π‘ plus nine cos squared three π‘.
00:01:35.691 --> 00:01:40.541
At this stage, we recall the trigonometric identity sin squared π‘ plus cos squared π‘ equals one.
00:01:40.841 --> 00:01:45.011
And we see that we have nine sin squared π‘ plus nine cos squared π‘.
00:01:45.141 --> 00:01:46.811
Well, that must be equal to nine.
00:01:47.001 --> 00:01:52.871
Similarly, we have nine sin squared three π‘ plus nine cos squared three π‘, which is also equal to nine.
00:01:53.071 --> 00:01:58.211
And we also have negative 18 times sin π‘ sin three π‘ plus cos π‘ cos three π‘.
00:01:58.311 --> 00:02:01.441
All Iβve done here is factored the negative 18 out.
00:02:01.691 --> 00:02:08.291
Next, weβre going to use the trigonometric identity cos of π΄ minus π΅ is equal to cos π΄ cos π΅ plus sin π΄ sin π΅.
00:02:08.411 --> 00:02:17.011
And this means that sin π‘ sin three π‘ plus cos π‘ cos three π‘ must be equal to cos of three π‘ minus π‘, which is, of course, simply cos of two π‘.
00:02:17.081 --> 00:02:20.921
So this becomes 18 minus 18 cos of two π‘.
00:02:21.081 --> 00:02:29.641
And so, we find that the arc length is equal to the definite integral between zero and π of the square root of 18 minus 18 cos of two π‘ dπ‘.
00:02:30.511 --> 00:02:32.851
Letβs clear some space and evaluate this integral.
00:02:33.101 --> 00:02:39.571
Now, in fact, the integral of the square root of 18 minus 18 cos of two π‘ still isnβt particularly nice to calculate.
00:02:39.741 --> 00:02:44.361
And so, we go back to the fact that cos of two π‘ is equal to two cos squared π‘ minus one.
00:02:44.651 --> 00:02:48.491
We replace cos of two π‘ with this expression and then distribute the parentheses.
00:02:48.491 --> 00:02:53.791
And our integrand is now equal to the square root of 36 minus 36 cos squared π‘.
00:02:54.101 --> 00:03:00.941
We take out the common factor of 36 and then rearrange the identity sin squared π‘ plus cos squared π‘ equals one.
00:03:01.051 --> 00:03:04.331
So that one minus cos squared π‘ is equal to sin squared π‘.
00:03:04.381 --> 00:03:10.941
So our integrand is six times the square root of sin squared π‘, which is, of course, simply six sin π‘.
00:03:11.101 --> 00:03:15.241
When we integrate six sin π‘, we get negative six cos π‘.
00:03:15.431 --> 00:03:19.941
So the arc length is equal to negative six cos π‘ evaluated between those limits.
00:03:20.021 --> 00:03:25.251
Thatβs negative six cos of π minus negative six cos of zero, which is equal to 12.
00:03:25.391 --> 00:03:30.171
And so, we found that the arc length of the curve that weβre interested in is 12 units.
00:03:31.471 --> 00:03:39.651
As you might expect, not only does this process work for curves defined by trigonometric equations, but also those defined by exponential and logarithmic ones.